Supervisor Developmental Feedback and Voice: Relationship or Affect, Which Matters? - Zhang, Zhenduo; Zhang, Li; Zheng, Junwei; Cheng, Bao; Rahmadani, Vivi Gusrini (Frontiers in Psychology, 2019)
Employee voice is the discretionary communication of ideas, suggestions, or concerns to benefit the organization. Employee voice is important for both organizations and employees. As such, this study examined the relationship between supervisor behavior and voice, by exploring the positive influences of supervisor developmental feedback on employee voice at the episode level. Further, this study explored the underlying mediators of positive affect and perceived rapport in the relationship between supervisor developmental feedback and employee voice, based on social exchange theory. The study collected 310 matched data points, collected across 62 employees for five consecutive days, using an experience sampling method with mobile surveys. Day-level supervisor developmental feedback positively related to day-level employee voice. Positive affect and perceived rapport with supervisors mediated the relationship between supervisor developmental feedback and employee voice at the episode level. The findings extend the antecedents of voice and examined the social exchange process at a within-person level.